Design and Evaluation of Android Slide Kyeboard for Myanmar Language - Nandar Pwint Oo; Ni Lar Thein (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
Because of the large character set nature of Myanmar character, currently used Myanmar language soft keyboard look like QWERTY layout on Android devices’s performance is degraded when using on small screens. The users are needed to switch keyboard layout frequently to get their desired characters. To reduce the user keyboard layout switching time, this paper proposed the slide keyboard to set the entire Myanmar character on one screen layout. User study was made by comparing slide keyboard with currently used Myanmar language soft keyboard that look like QWERTY layout (iTextMM). The user preferences and empirical evaluation is also analyzed. According to the evaluation, the parpicipants can take minimum learning time with slide keyboard and can type at a rate of 17 Character per Minutes (CPM) and have got average 0.65 error rates.DOI: http://dx.doi.org/10.11591/ij-ict.v1i2.1378